A consistency elasto-viscoplastic damage model for progressive failure analysis of composite laminates subjected to various strain rate loadings. (15th July 2016) - Chen, Jing-Fen; Morozov, Evgeny V.
Abstract: This paper is concerned with the development and validation of a consistency elasto-viscoplastic damage model that accounts for the strain rate-dependent plastic response and the progressive post-failure behaviour of composite materials. The model proposed is suitable for progressive failure analysis of composite materials and structures subjected to loadings at various strain rates. A strain rate-dependent yield criterion is adopted; whereas the standard Kuhn–Tucker conditions for plastic loading and unloading remain valid. Also, the plastic consistency condition for strain rate-dependent material is satisfied. The relevant strain-driven implicit numerical integration procedure for the proposed material model is developed. A tangent stiffness operator including the strain rate-dependent effects and consistent with the integration procedure developed is derived to ensure the quadratic convergence rate pertaining to the Newton–Raphson method in a finite element analysis. The implicit integration algorithm is implemented in the finite element code Abaqus through the user-defined material subroutine UMAT. The validation of the proposed model is performed on S2/8552 glass/epoxy off-axis block composite specimens subjected to compression at various strain rates. It is shown that the strain rate-dependent response of composite materials is well captured and the predicted results agree well with the experimental data reported in the literature.